2000
DOI: 10.1002/1529-0131(200011)43:11<2550::aid-anr24>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial cell apoptosis in systemic sclerosis is induced by antibody-dependent cell-mediated cytotoxicity via CD95

Abstract: The results suggest that endothelial cell apoptosis in SSc is induced by antibody-dependent cell-mediated cytotoxicity via the Fas pathway. These data not only provide insight into the pathogenesis of SSc, but also may open new ways to rational therapy for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
105
0
5

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 209 publications
(116 citation statements)
references
References 56 publications
4
105
0
5
Order By: Relevance
“…NK cells (47) and gd cells (48) were reported as the mediators of the cytotoxicity; however, it remains unclear whether CD8 + T cells are involved in endothelial cell injury. On this point, we observed that the cytotoxic capacity of CD8 + T cells against endothelial cells was upregulated in SSc patients.…”
Section: Discussionmentioning
confidence: 99%
“…NK cells (47) and gd cells (48) were reported as the mediators of the cytotoxicity; however, it remains unclear whether CD8 + T cells are involved in endothelial cell injury. On this point, we observed that the cytotoxic capacity of CD8 + T cells against endothelial cells was upregulated in SSc patients.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, and as opposed to myofibroblasts, increased EC apoptosis has been reported to play a primary pathogenic role in various fibrotic diseases such as chronic rejection of solid organ transplants, graft-versus-host disease and systemic sclerosis. 4,5,25 The fibrogenic pathways elicited by EC apoptosis are still poorly defined. Here, we aimed at evaluating whether paracrine mediators produced by apoptotic ECs could activate fibrogenic pathways in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Endothelial cell (EC) apoptosis is increasingly recognized as an early pathogenic event in fibrosis. A wide array of fibrogenic conditions, such as systemic sclerosis, 4,5 graftversus-host disease 6,7 and chronic rejection of solid allografts, 8,9 has been associated with increased EC apoptosis. Pathophysiological pathways linking endothelial apoptosis to fibrogenesis are still poorly defined.…”
mentioning
confidence: 99%
“…The basic science studies, integrated with clinical evaluation of SSc patients, are direct to identify either new biological disease marker(s) suitable for clinical practice or new signaling pathways involved in the pathogenesis of SSc disease [5,7].…”
Section: Introductionmentioning
confidence: 99%